Electron Paramagnetic Resonance Study of Ternary CuII Compounds with Glycine and Phenanthroline - Santana, Ricardo C. (2014)
We report electron paramagnetic resonance (EPR) measurements at 9 and 34 GHz, and room temperature (T), in powder and single crystal samples of the ternary compounds of copper nitrate or copper chloride with glycine and 1,10-phenanthroline [Cu(Gly)(phen)(H2O)]∙NO3∙1.5H2O (1) and [Cu(Gly)(phen)Cl]2∙7H2O (2). In compound 1 the copper ions are arranged in 1-D chains along one of the crystal axes connected by syn-anti carboxylate ligands, while in 2 the array is nearly 3-D and the connections involve H-bonds and stacking interactions. The angular variation of the squared g-factor and the line width were measured as a function of orientation of the magnetic field (B0) in three orthogonal crystal planes. In both compounds we observed one resonance without hyperfine structure for any magnetic field orientation which we attribute to the collapse of the hyperfine coupling and of the resonances of two chemically identical but rotated coppers in the unit cell, produced by exchange interactions. We analyze the results in terms of the structures of the compounds and of the chemical paths connecting neighbor copper ions which support the exchange interactions between neighbor spins in the lattice. Considering the collapse of the EPR signals of rotated sites in the lattices we are able to set lower  limits to the exchange interactions, which are supported by weak equatorial-apical carboxylate bridges in 1, and by paths containing hydrogen bonds and aromatic interactions in 2. Broadening due to dipole dipole couplings and hyperfine interactions are strongly reduced by these exchange couplings and their role in the EPR line width is more difficult to recognize.